PENGARUH BEBAN KERJA, STRES KERJA, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA ERA PANDEMI - Nugraheni, Devia Jeanindita; Sutrisno, Sutrisno; Setyorini, Noni (Lembaga Pengembangan Kinerja Dosen, 2023)
Abstract. This study aims to examine the influence of Workload, Work Stress, Work Environment, and Employee Compensation and Performance at the Pandanaran Hotel Semarang in the Covid-19 Pandemic Era. The technique used in this study is non-probability sampling and is processed using multiple linear regression techniques. The results of the analysis and discussion based on questionnaires distributed to 114 respondents show that workload and work stress partially have a significant effect on employee performance. While the work environment and compensation variables partially have a positive and significant influence on the performance of Hotel Pandanaran Semarang employees in the Covid 19 Pandemic Era.